Understanding Organisational Factors and Models to Support Corporate Entrepreneurship in Business Organisation – Some Case Studies - Atreja, Ankit (2014)
Purpose of business is business - to make money. World today offers very dynamic and challenging environment. There have been periods of economic recession which have slowed down growth but have also given rise to various new entrepreneurial start-ups whose daring entrepreneur, visionary leader took advantage and changed those challenges into opportunities, when no one else dared. They proved their acumen and with the passage of time took/grew their small start-up into giants like Cargill, Siemens, General Mills etc. At this stage the small start-up is said to have undergone and completed its metamorphosis as it evolved into bureaucratic, multi hierarchy, and rigid structure, which tend to slow down the very essence of its existence - its entrepreneurial and innovative spirit, which took it from nowhere to somewhere. This report delves into subject of Corporate Entrepreneurship which is about corporations keeping the flame of entrepreneurship and innovation kindled. This report studies various types, essential dimensions, and various organisational factors associated with CE and are indicated to promote CE within an organisation. Also various models which ategorise/define such deliberate efforts practiced by organisations to breathe life into its organisations entrepreneurial spirit and to achieve growth and competitive advantage. In order to evaluate CE this research adopts qualitative based approach to decipher the norms and practices of nine large established multinational corporations. It gleans out crucial organisational factors and CE models prominent within these corporations. Findings revealed that there are various ways in which organisations fund and drive entrepreneurial and innovation initiatives within the organisation and the ownership of new business creation (here the newness was reflected through different forms of outcomes) was either diffused i.e., dispersed teams or focused i.e., dedicated team/units. All these organisations indicated to have been promoting CE through one or more of the factors which the existing literature had highlighted. Based on these findings and utilising the concepts discussed in literature a framework was created to provide a holistic view of CE. The significance of this research is that it will be precursor to the future research in this area and will augment business organisation's strategy.